Radiologic characteristics and management of screen-detected metastatic carcinoid tumor of the breast: a case report. - Adams, R; Parulekar, V; Hughes, C; Kadour, M; Talbot, D (Elsevier, 2009)
Carcinoid tumors are known to metastasize to the breast, but their appearance can mimic a primary breast carcinoma, making biopsy essential in order to give the correct preoperative diagnosis. It has been suggested that core biopsy might precipitate a carcinoid crisis and should be avoided. We describe a case of screen-detected carcinoid tumor metastasis in the breast safely diagnosed by core biopsy and present the imaging findings, including magnetic resonance imaging and elastography. This case illustrates the importance of preoperative histologic diagnosis in enabling the appropriate surgical or medical management of these patients. Review of the literature also supports the policy that biopsy of nonhormonally active tumors may be safely performed.